2014
DOI: 10.1088/1475-7516/2014/06/029
|View full text |Cite
|
Sign up to set email alerts
|

Perturbations of nested branes with induced gravity

Abstract: We study the behaviour of weak gravitational fields in models where a 4D brane is embedded inside a 5D brane equipped with induced gravity, which in turn is embedded in a 6D spacetime. We consider a specific regularization of the branes internal structures where the 5D brane can be considered thin with respect to the 4D one. We find exact solutions corresponding to pure tension source configurations on the thick 4D brane, and study perturbations at first order around these background solutions. To perform the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(57 citation statements)
references
References 50 publications
2
55
0
Order By: Relevance
“…A similar cascading behavior of the force law was also obtained recently in a different codimensiontwo framework [782]. Closely related work on intersecting branes was discussed in [783][784][785] with somewhat different motivations. See [780,786,787] for studies of degravitation in the cascading framework, and [788] for self-accelerated solutions in this context.…”
Section: Degravitationsupporting
confidence: 74%
“…A similar cascading behavior of the force law was also obtained recently in a different codimensiontwo framework [782]. Closely related work on intersecting branes was discussed in [783][784][785] with somewhat different motivations. See [780,786,787] for studies of degravitation in the cascading framework, and [788] for self-accelerated solutions in this context.…”
Section: Degravitationsupporting
confidence: 74%
“…In the past years, several interesting properties of the model were uncovered, such as a better behaviour concerning ghost instabilities [12][13][14] than that of the pure codimension-2 set-up with induced gravity [15] (see, however, [16]). Moreover, it was proposed that the codimension-1 brane acts somehow as a regulator, rendering gravity finite at the codimension-2 brane even when its thickness tends to zero [17,18]. However, a mathematically clean proof of these properties, as well as the general investigation of exact solutions, were made impossible by the well-known issue that the thin limit of a codimension-2 brane is not well-defined [19].…”
Section: The 6d Cascading Dgp Modelmentioning
confidence: 99%
“…Furthermore, it can be shown that the thin limit of the ribbon brane (inside the already thin codimension-1 brane) is well dened [23]. It follows that, with this assumption about the hierarchy of the thicknesses, we can indeed work with thin branes and forget the internal structures.…”
Section: The Nested Brane Realization Of the Cascading Dgp Modelmentioning
confidence: 91%
“…These background solutions are most naturally expressed in a bulk-based approach, where the bulk metric is at and the codimension-1 embedding has a cusp at the codimension-2 brane [23].…”
Section: Perturbations Around Pure Tension Solutionsmentioning
confidence: 99%